PERUBAHAN LUASAN MANGROVE DAN HUBUNGANNYA DENGAN PRODUKSI PERIKANAN DI KOTA LANGSA PROVINSI ACEH (Changes of Mangrove Area and Its Relation to Fishery Production in Langsa City, Province Aceh - Antasari Malau; Budi Utomo; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The purpose of this research is aimed to get information for the relation of mangrove ecosystem and fishery resources in Langsa City. This research used descriptive method based on land cover, regression and correlation analysis. Types of data used in this research were primary data of observation and interview, secondary data of mangrove fish catching result and mangrove area change from Landsat. The result shown that the mangrove change area of the period from 2011 to 2016 has decreased by 84 ha as well as the production of fishery resources from mangroves was from 2011 amounted to 1,762 tons decreasing became 414.4 tons in 2016. There was a real influence between the change of mangrove forest area to the production of fishery resources as yielding the equation y = 11,82x - 46427 with the correlation coefficient 0,73. Thus, the production of fish, shrimp or crabs is influenced by the area of mangrove forest, and the more extensive mangrove forest, production is also higher.Keywords: fishery resources, mangrove, land cover, Langsa city